2007
DOI: 10.1209/0295-5075/80/18002
|View full text |Cite
|
Sign up to set email alerts
|

Cooperative behavior in a model of evolutionary snowdrift games with N-person interactions

Abstract: We propose a model of evolutionary snowdrift game with N -person interactions and study the effects of multi-person interactions on the emergence of cooperation. An exact N -th-order equation for the equilibrium density of cooperators x * is derived for a well-mixed population using the approach of replicator dynamics. The results show that the extent of cooperation drops with increasing cost-to-benefit ratio and the number N of interaction persons in a group, with x * ∼ 1/N for large N . An algorithm for nume… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
81
0
2

Year Published

2010
2010
2021
2021

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 108 publications
(92 citation statements)
references
References 27 publications
3
81
0
2
Order By: Relevance
“…Zheng et al [88] studied an N-person Snowdrift game with cost sharing among contributors. They showed that cooperators can be maintained in the population at a small frequency (approximately 1/n with large n).…”
Section: (I) Homogeneous Groupsmentioning
confidence: 99%
“…Zheng et al [88] studied an N-person Snowdrift game with cost sharing among contributors. They showed that cooperators can be maintained in the population at a small frequency (approximately 1/n with large n).…”
Section: (I) Homogeneous Groupsmentioning
confidence: 99%
“…Within the area of dynamics, two-player games [14][15][16] are frequently adopted to model typical pairwise interactions to understand the evolution of cooperation [17][18][19][20][21][22][23][24][25][26]. Considering the ubiquitously group interactions ranging from the natural world to human society, researchers recently generalized two-player games to their multiplayer versions [27][28][29][30][31][32][33][34][35][36][37], such as the N -person prisoner's dilemma [30,38], N-person snowdrift game [31,32], N -person stag hunt game [39], as well as the N -person ultimatum game [40]. In a typical collective action, an individual's payoff could be no longer the simple summation of many pairwise interactions [33,41], and instead it is replaced by the multiple interactive payoffs from multiplayer games, which depends on what strategies all other opponents hold in the same group.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, as we consider general group interactions in structured populations, we are provided with a much greater chance to explore the effects of population structure on the evolution of cooperation. However, due to its inherent complexity, until now the evolutionary dynamics has only been given for some specific games or well-mixed populations [12,31,32,39,44,45,48,53,54]. Here we give the evolutionary dynamics for an arbitrary multiplayer game with two strategies in structured populations represented by regular…”
Section: Introductionmentioning
confidence: 99%
“…Both individuals of a cooperative partnership might therefore play a mixed strategy of either cooperating or conflicting with their counter-partners, and whether they cooperate or conflict might only depend on the direct benefit received in a given situation [18][19][20][21]. In a system with limited dispersal or exit cost for the individuals involved, the more difficult it is for the involved individuals to disperse to other colonies or groups, the more viable the sanction of the dominate or host against the non-cooperative subordinate will be [7,9,39,40]. The subordinate or symbiont might therefore tend to cooperate with the dominate in such a system.…”
Section: Resultsmentioning
confidence: 99%